Feminist utopias and struggles: The case of achieving the decriminalization of abortion in the State of Guerrero (2021-2023) - DE LA ROSA PALAFOX, Angie (Utopía y Praxis Latinoamericana, 2025)
This research describes and explains the struggles of feminist collectives and organizations to achieve the decriminalization of abortion in the State of Guerrero, during the period 2021-2023. It is theorized, in this sense, that the application of citizenship to reproductive rights and to decide about our bodies was a product of the confluence of the following factors: The maturation and crystallization of collective action and a coalition of intergenerational feminist collectives possessing collective resources, institutional and informal with the capacity to influence the decisions of political institutions such as the Congress of the State of Guerrero; The existence of allies in the State Congress and the configuration of the women’s struggle that deployed the feminist movement, positively influenced the historic achievement of the local legislative reform that allowed us to appropriate our autonomy and reproductive rights through the decriminalization of abortion in the entity.